Tap water quality: in the eye of the beholder - Arnt O. Hopland; Sturla F. Kvamsdal (IWA Publishing, 2022)
The quality of tap water is important. We consider whether objective measures of water quality factor into satisfaction with tap water among a large sample of Norwegian citizens. Our data include over 40,000 observations from the last decade and constitute an unprecedented empirical basis for investigating the link between water quality and user satisfaction. Objective measures of water quality include tests on Escherichia coli, intestinal enterococci, pH, and color. Only color has a significant impact on citizens' satisfaction with tap water. However, individual characteristics can to some degree predict tap water satisfaction. For example, the general level of satisfaction with public services and society, age, education, income, and gender are relevant characteristics. Our data are rich enough to allow for the use of fixed effects to control for unique municipal factors, such as geography and access to water sources, as well as time trends. Thus, we provide rather solid evidence that satisfaction with tap water is unrelated to several objective measures of quality, but that satisfaction is related to several individual characteristics. HIGHLIGHTS Compare objective measures of tap water quality with user satisfaction.; Extensive, nationwide panel data.; Only a weak link between objective quality and user satisfaction.; Individual user characteristics are strong predictors of user satisfaction.;